Evaluasi Ketepatan Antipsikotik pada Pasien Skizofrenia di Instalasi Rawat Inap Rumah Sakit Jiwa Daerah Atma Husada Mahakam Samarinda - Khofifah Nurwahidah Balqis; Mukti Priastomo; Adam M. Ramadhan (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
Schizophrenia is a psychotic mental disorder that causes psychiatric symptoms, such as confusion in thinking, emotions, perceptions, and deviant behavior. The purpose of this study was to determine the characteristics, pattern of use of antipsychotic drugs, and evaluation of the accuracy of antipsychotics for schizophrenia patients in the inpatient installation of RSJD Atma Husada Mahakam Samarinda including the right indication, the right patient, the right drug selection, the right dose, the right frequency and the right duration. administration based on Pharmacotherapy Handbook Tenth Edition Algorithms and Formularium schizophrenia at RSJD Atma Husada Mahakam Samarinda. This type of research is observational. The data collection was done retrospectively with the sampling technique with total sampling on medical records at RSJD Atma Husada Mahakam Samarinda. The results of The most prescribed antipsychotics in schizophrenia patients was the administration of a single antipsychotic risperidone (21.51%), and the administration of a clozapine-risperidone combination antipsychotic (20.43%). Accuracy of antipiscotic use with precise parameters of indication, patient, drug selection, dose, frequency of administration and exact duration of administration based on the Pharmacotherapy Handbook Tenth Edition Algorithms and formulary at RSJD Atma Husada Mahakam Samarinda is 100% accurate from the 93 drug prescriptions studied.